Corpo-território cambiante e processos híbridos no contexto da arte contemporânea - Aranha, Luise Dolinski (2015)
How to think the body as territory in a poetic production in the context of contemporary art with a focus on art and technology? This subject was guiding for the present investigation and moved the poetic doing that I propose to think the body as territory, as a place of intensive power, moved by a complexity of shifting forces that performs folds and pleats of skins on the plan of sensations, emotions, feelings and desires.The skins understood as layers that imprisons intensities, but reveal themselves as nomads‟ subjectivities that breaks and opens cracks in this passageway and reveals a territory in becoming, as well as inaugurates the construction of new modes of existence in power with life.Thus, the work is constituted in a research and production in the field of art and technology,from the language of photography, discussed in hybrid processes of image construction through digital manipulation, resulting in a set of images printed that matches with projected images operatingmodes that open paths to an aesthetic focused on flexibility, mobility and multiplicity.The body is inserted as a visual element that wear skins that disguise it, as well as protects it, involves it, builds it and, at the same time, deconstructs it, remaking it into a process of "birth and death".